Ultra‐Low Threshold Titanium‐Doped Sapphire Whispering‐Gallery Laser. Issue 8 (11th March 2022) - Azeem, Farhan; Trainor, Luke S.; Gao, Ang; Isarov, Maya; Strekalov, Dmitry V.; Schwefel, Harald G. L.
Abstract: Titanium doped sapphire (Ti:sapphire) is a laser gain material with broad gain bandwidth benefiting from the material stability of sapphire. These favorable characteristics of Ti:sapphire have given rise to femtosecond lasers and optical frequency combs. Shaping a single Ti:sapphire crystal into a millimeter sized high quality ( Q ) whispering gallery mode resonator ( Q ≈ 10 8 ) reduces the lasing threshold to 14.2 mW and increases the laser slope efficiency to 34%. The observed lasing can be both multi‐mode and single‐mode. This is the first demonstration of a Ti:sapphire whispering‐gallery laser. Furthermore, a novel method of evaluating the gain in Ti:sapphire in the near infrared region is demonstrated by introducing a probe laser with a central wavelength of 795 nm. This method results in decreasing linewidth of the modes excited with the probe laser, consequently increasing their Q . These findings open avenues for the usage of whispering gallery mode resonators as cavities for the implementation of compact Ti:sapphire lasers. Moreover, Ti:sapphire whispering‐gallery laser can also be utilized as an amplifier inside its gain bandwidth by implementing a pump–probe configuration. Abstract : A fresh approach is taken to titanium sapphire by manufacturing it into a whispering‐gallery laser. The new monolithic form factor allows lasing at a record low threshold power with a high slope efficiency. Gain in the active resonator is accurately measured through the linewidth of the whispering‐gallery modes.